Landscape and the visual hermeneutics of place, 1500-1700 - Enenkel, K. A. E.; Melion, Walter S. (Intersections : interdisciplinary studies in early modern culture, 2021)
"This volume examines the image-based methods of interpretation that pictorial and literary landscapists employed between 1500 and 1700. The seventeen essays ask how landscape, construed as the description of place in image and/or text, more than merely inviting close viewing, was often seen to call for interpretation or, better, for the application of a method or principle of interpretation"--